The Influence of Parenting Patterns on Adolescents' Emotional Intelligence: Pola asuh - SALSABILA, Jihan Hasna (Journal of Social Sciences and Cultural Study, 2024)
Adolescence represents a critical transitional phase from childhood to adulthood and serves as a key stage in the human life development cycle. This period is characterized by significant hormonal changes, leading to various physical, emotional, and psychological transformations. Among these, emotional changes are particularly noteworthy as they directly relate to the development of emotional intelligence, a crucial skill influencing an individual's ability to manage emotions, build relationships, and navigate social interactions. Emotional intelligence is shaped by various factors, with parenting patterns emerging as a particularly influential determinant. This study aims to investigate the extent to which different parenting patterns impact the emotional intelligence of middle-aged adolescents. This study uses a qualitative methodology, with observations and interviews serving as the main means of gathering data. The study's respondents consist of six middle-aged adolescents, comprising both male and female participants, selected to provide diverse perspectives. The findings reveal that parenting patterns play a pivotal role in shaping the emotional intelligence of adolescents. Adolescents who experience supportive, nurturing, and consistent parenting tend to exhibit higher levels of emotional intelligence, including improved self-awareness, empathy, and emotional regulation. Conversely, inconsistent or neglectful parenting may hinder the development of these skills. The study underscores the importance of parental involvement and adaptive parenting strategies during adolescence to foster emotional intelligence. These findings provide valuable insights for parents, educators, and practitioners working with adolescents, emphasizing the need for a supportive environment to promote holistic development during this critical life stage.